2017
DOI: 10.1016/j.ydbio.2017.03.033
|View full text |Cite
|
Sign up to set email alerts
|

Xenopus egg extract: A powerful tool to study genome maintenance mechanisms

Abstract: DNA repair pathways are crucial to maintain the integrity of our genome and prevent genetic diseases such as cancer. There are many different types of DNA damage and specific DNA repair mechanisms have evolved to deal with these lesions. In addition to these repair pathways there is an extensive signaling network that regulates processes important for repair, such as cell cycle control and transcription. Despite extensive research, DNA damage repair and signaling are not fully understood. In vitro systems such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 110 publications
0
36
0
Order By: Relevance
“…First, we assessed whether FA-RAD51 mutations alleviate protection of nascent DNA at stalled RF using Xenopus laevis cellfree egg extracts-a well-established system for studying DNA replication and genome maintenance-associated functions of proteins with a high degree of conservation between Xenopus and human proteins (Hoogenboom et al, 2017;Sannino et al, 2016). Xenopus extracts containing replicating chromatin were exposed to a short pulse of biotin-labeled dUTPs, followed by an aphidicolin (APH) treatment, and the remaining biotin in the nascent DNA was then quantified at various time points (Figure 1A) (Kolinjivadi et al, 2017).…”
Section: Fa-rad51 Mutants Are Defective At Protection Of Stalled Rfmentioning
confidence: 99%
“…First, we assessed whether FA-RAD51 mutations alleviate protection of nascent DNA at stalled RF using Xenopus laevis cellfree egg extracts-a well-established system for studying DNA replication and genome maintenance-associated functions of proteins with a high degree of conservation between Xenopus and human proteins (Hoogenboom et al, 2017;Sannino et al, 2016). Xenopus extracts containing replicating chromatin were exposed to a short pulse of biotin-labeled dUTPs, followed by an aphidicolin (APH) treatment, and the remaining biotin in the nascent DNA was then quantified at various time points (Figure 1A) (Kolinjivadi et al, 2017).…”
Section: Fa-rad51 Mutants Are Defective At Protection Of Stalled Rfmentioning
confidence: 99%
“…Xenopus egg extracts have a long track record of dissecting nuclear dynamics and interrogating processes such as DNA replication, chromosome segregation, and DNA repair (Heald et al, 1996; Hoogenboom et al, 2017; Kalab et al, 2006; Knipscheer et al, 2009; Lebofsky et al, 2009). We therefore used high-speed supernatant (HSS) of total Xenopus laevis egg lysate (Lebofsky et al, 2009) to look for cellular factors that promote the dissociation of a pre-formed Cas9 RNP-DNA complex.…”
Section: Resultsmentioning
confidence: 99%
“…Many regulators of ATR accumulate on chromatin in egg extracts upon replication stress [25,[32][33][34]. By mass spectrometry analysis, Haahr et al [21] observed enrichment of ETAA1 on chromatin following treatment with the DNA polymerase inhibitor aphidicolin (APH).…”
Section: Xenopus Etaa1 Associates With Chromatin In a Checkpoint-depementioning
confidence: 99%